The expression x^2 + y^2 - 6x + 8y + 9 = 0 is the equation of a circle.

The standard form of a circle is (x - a)^2 + (y - b)^2 = r^2, where r is the radius of the circle and (a,b) is the center.

x^2 + y^2 - 6x + 8y + 9 = 0

=> x^2 - 6x + y^2 + 8y + 9 = 0

=> x^2 - 6x + 9 + y^2 + 8y + 16 = 9 + 16 - 9

=> (x - 3)^2 + (y + 4)^2 = 4^2

**The standard form of the equation of the circle is (x - 3)^2 + (y +
4)^2 = 4^2**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.